(untitled) (The International Journal for Scientific Research, 2025)
The scientific review aimed to shed light on the most important previous studies related to the causes of delayed marriage in light of youth trends towards marriage in public libraries; by presenting the problem of the scientific review and its objectives, limits, and the topics that were reviewed, and under each sub-topic, the chronological arrangement was made from the newest to the oldest. The review also addressed the research terms related to the causes of delayed marriage, youth trends towards marriage, sources of research on it, and quantitative characteristics of intellectual production. The scientific review included 4 axes, which were represented in total in (29) studies, including (3) foreign studies, (26) Arab studies, commenting on the studies and interpreting their results, and presenting the points of agreement and difference between previous studies that addressed the causes of delayed marriage and youth trends towards marriage in public libraries.